Effectiveness of Bacillus thuringiensis (Bt) application in controlling mortality of Spodoptera litura on rice plants (Oryza sativa L.) - Sembiring, Jefri; Mendes, Johana; Kusumah, Rangga; Susanti, Diana Sri; Anwar, Anwar; Sarijan, Abdullah; Yusuf, Mani (Anjoro: International Journal of Agriculture and Business, 2024)
Rice (Oryza sativa L.) is the primary commodity for the Indonesian people because most of the Indonesian population depends on rice. The armyworm pests Spodoptera litura causes irregular holes in the leaves, thus disrupting the photosynthesis process and reducing rice production, so it is necessary to treat the pest. Bacillus thuringiensis is a pathogenic bacterium for insects, such as S. litura. This study aimed to look at the effectiveness of B. thuringiensis on the mortality of S. litura on a laboratory and field scale. The research was conducted in the Agrotechnology Laboratory, Faculty of Agriculture, Musamus University. The research design was a complete randomized design (RAL). The research study was conducted on five treatment doses of B. thuringiensis, which were 20 g/500 ml of water; 40g/500 ml of water; 60 g/500 ml of water; 80 g/500 ml of water; 100 g/500 ml of water. Each treatment was repeated five times. The results showed that, applying B. thuringiensis can significantly decrease the population and intensity of S. litura. The highest mortality rate in laboratory trials was observed at a dose of 100 grams/500 ml of water, with 50 dead individuals. In contrast, the lowest mortality rate was recorded at a dose of 20 gram of material/500ml of water, with only 12 death S. litura larvae. In field testing, the best dose was 50 gram/14 liters of water, and it caused the death of 50 S. litura larvae. Spraying B. thuringiensis on rice plants can reduce the population and intensity of S. litura.